Role of SN1 lipases on plasma lipids in metabolic syndrome and obesity - Miksztowicz, Veronica Julieta (2014)
Objective—To assess the phospholipase activity of endothelial (EL) and hepatic lipase (HL) in postheparin plasma of subjects with metabolic syndrome (MS)/obesity and their relationship with atherogenic and antiatherogenic lipoproteins. Additionally, to evaluate lipoprotein lipase (LPL) and HL activity as triglyceride (TG)-hydrolyses to complete the analyses of SN1 lipolytic enzymes in the same patient. Approach and Results—Plasma EL, HL, and LPL activities were evaluated in 59 patients with MS and 36 controls. A trend toward higher EL activity was observed in MS. EL activity was increased in obese compared with normal weight group (P=0.009) and was negatively associated with high-density lipoprotein–cholesterol (P=0.014 and P=0.005) and apolipoprotein A-I (P=0.045 and P=0.001) in control and MS group, respectively. HL activity, as TG-hydrolase, was increased in MS (P=0.025) as well as in obese group (P=0.017); directly correlated with low-density lipoprotein–cholesterol (P=0.005) and apolipoprotein B (P=0.003) and negatively with high-density lipoprotein–cholesterol (P=0.021) in control group. LPL was decreased in MS (P<0.001) as well as in overweight and obese compared with normal weight group (P=0.015 and P=0.004, respectively); inversely correlated %TG-very low-density lipoproteins (P=0.04) and TG/apolipoprotein B index (P=0.013) in control group. These associations were not found in MS. Conclusions—We describe for the first time EL and HL activity as phospholipases in MS/obesity, being both responsible for high-density lipoprotein catabolism. Our results elucidate part of the remaining controversies about SN1 lipases activity in MS and different grades of obesity. The impact of insulin resistance on the activity of the 3 enzymes determines the lipoprotein alterations observed in these states.